2016
DOI: 10.1088/1758-5090/8/3/035016
|View full text |Cite
|
Sign up to set email alerts
|

Novel integrative methodology for engineering large liver tissue equivalents based on three-dimensional scaffold fabrication and cellular aggregate assembly

Abstract: A novel engineering methodology for organizing a large liver tissue equivalent was established by intergrating both 'top down' and 'bottom up' approaches. A three-dimensional (3D) scaffold was engineered comprising 43 culture chambers (volume: 11.63 cm(3)) assembled in a symmetrical pattern on 3 layers, a design which enables further scaling up of the device to a clinically significant size (volume: 500 cm(3)). In addition, an inter-connected flow channel network was designed and proved to homogenously deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The oxygen supply through the PDMS membrane was two orders of magnitude higher than that through the culture medium (41). Based on this difference, we generated high-density cultures of hepatocytes in our previous studies (36,37,39,42). Here, utilizing the same microwell device, we successfully acquired cell aggregates with a cell density of 4.0×10 6 cells/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen supply through the PDMS membrane was two orders of magnitude higher than that through the culture medium (41). Based on this difference, we generated high-density cultures of hepatocytes in our previous studies (36,37,39,42). Here, utilizing the same microwell device, we successfully acquired cell aggregates with a cell density of 4.0×10 6 cells/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of their later relevant studies, cell viability in the culture system decreased to less than 60% after just one day (28). Aiming to solve this problem, we proposed the idea of "looselypacked hepatic tissue elements" in our previous studies (36,37). We used biodegradable scaffold fibers and made a mixture with formed hepatic cell aggregates in a perfusion culture system, which has been proved to be a simple and effective way of maintaining the interstitial space.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative methods were established for generating scaffolds with defined pore sizes and pore distributions, such as fused deposition modeling, 93 selective laser sintering, 94 stereolithography (SLA), 95 and 2-PP. 96 These so-called RP techniques are manufacturing techniques in which 3D structures are generated in a LbL manufacturing process.…”
Section: Methods Used For Scaffold Productionmentioning
confidence: 99%
“…116 It was also demonstrated that cell response could be improved when seeding cells using perfusion bioreactors. 94…”
Section: Designer Scaffolds Based On Tpmssmentioning
confidence: 99%
“…Despite the relatively high postoperative survival rate, there are many problems to be solved, however, including a chronic donor shortage, immune rejection, and ethical issues. Therefore, cell-based regenerative therapies and novel technologies such as liver-on-chip [4] and bioprinted liver [5] are expected to be the next-generation therapies.…”
Section: Introductionmentioning
confidence: 99%